Bacteriological Profiles of Pus with Antimicrobial Sensitivity Pattern at a Teaching Hospital in Dhaka City - Khanam, Rashida Akter; Islam, Md Rafiqul; Sharif, Ahmed; Parveen, Rezina; Sharmin, Ishrat; Yusuf, Md Abdullah (Bangladesh Journal of Infectious Diseases, 2018)
Background: The human skin and soft tissue infections (SSTIs) caused by microbial pathogens during or after trauma, burn injuries, and surgical procedures result in the production of pus, a white to yellow fluid comprised of dead WBCs, cellular debris, and necrotic tissues. Objective: The purpose of the present study was to see the frequency and distribution of bacteria isolated from pus and sensitivity pattern. Methodology: This retrospective study was conducted in the Department of Microbiology at Shaheed Suhrawardy Medical College, Dhaka from January 2016 to December 2016 for a period of one (01) year. The pus samples were collected from the patients who were visited in outpatient department and were admitted at IPD in Shaheed Suhrawardy Medical College Hospital (ShSMCH), Dhaka with skin and soft tissue infection. Bacteria were detected by culture and biochemical test and antibiotic susceptibility test done by disc diffusion method. Result: A total number of 212 patients presented with wound infection or pus were recruited for this study. Among 212 patients majority were in the age group of 20 to 40 years which was 89(42.0%) cases. Interestingly male was predominant than female which was 119(56.1%) cases and 93(43.9%) cases respectively. aerobic culture was positive in majority cases which were 131(61.8%) cases. Conclusion: In conclusion the most common isolated bacteria after aerobic culture of pus is the Staphylococcus aureus. However the gram positive cocci is less in number than gram negative bacilli. Bangladesh Journal of Infectious Diseases 2018;5(1):10-14